Perlindungan Hukum terhadap Pelaku Pembunuhan Begal atas Dasar Pembelaan Terpaksa - Anak Agung Gede Agung; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
A criminal act is an act that is prohibited by law and is subject to sanctions. Not all acts that violate the provisions of the law can be punished, as contained in article 49 of the Criminal Code, which has been sentenced to a criminal sentence. A person who is a victim of a criminal act of tampering in the proximity of a criminal act who commits an act of defense is not sentenced. The type of research used is normative legal research. An act of defense that cannot be subject to punishment, the law applicable to article 49 of the Criminal Code in which a criminal act is committed in a threatening situation or an attack at that time, such as a victim of tampering himself, a judge as a law enforcer who examining and deciding an action can see evidence of the perpetrator's actions of self-defense which meet the elements of defense, the judge also considers the reasons of the perpetrator which can mitigate especially the perpetrator who is defending himself To law enforcement officials, judges in defending offenders who pay more attention to someone who is doing it so that justice can be created.